Pengaplikasian Hunian Green Design secara Sederhana untuk Menghadapi Dampak yang Ditimbulkan Pandemi - Anwar, Hendi; Naufal, Moch Fatin Abdul; Abdulhadi, Reza Hambali Wilman (Waca Cipta Ruang, 2023)
One major objective of the green design philosophy that many homes have embraced these days is lessening the effects of global warming. This is due to the fact that architecture is one of the main causes of global warming. A global quarantine involving severe limitations on human movement was implemented in 2021 because to the COVID-19 pandemic, and homes were turned into places where people may engage in a variety of activities throughout the clock. This is due to the COVID-19 virus, which is indiscriminate in its transmission and dangerous to human life, particularly in immunocompromised individuals. In the ongoing pandemic, significant efforts have been made to halt the COVID-19 virus's spread. Benefits of green design have been found to extend beyond reduced energy use and global warming. In particular, it mitigates the COVID-19 virus's effects on housing, which is one method it prevents the virus from propagating. Through a number of journal reviews and prior research studies, this qualitative study examines the relationship between green design principles and human health and how to implement them in housing. Simple green design implementations in residential buildings are expected to mitigate the COVID-19 pandemic's effects, particularly with regard to the health of the occupants.